Gidronima and gidronimny appellatives in I.Zhansugurov's works (Eurasian Journal of Philology Science and Education, 2015)
In this article the descriptive characteristic is given to hydro-names the names of reservoirs, from the origin point of view which is mentioned in I.Zhansugurov's works as «Zhetysu's Picture», «Kyuy», «Kyuyshy», «Makpal», «Isatay». It is defined functions of hydro-names, narrating about the events which were taking place in different regions of the country. They testify the historical reliability of events. From a material of article it is possible to receive information from history, feature of world vision of Kazakhs and their life. Often used appellatives as «water», «spring», «lake» are analyzed and reveal their values, etymology. The appellative «water» in Turkic languages is given in the shape of «sub», «sug», «suw», in the meaning of «river», «lake», «spring».
Keywords: etymology; hydro-names; hydrolytic appellative; onomastics; toponym; morpheme